Impact of Alcaligin Siderophore Utilization on In Vivo Growth of Bordetella pertussis - Brickman, Timothy J. (American Society for Microbiology (ASM), 2007)
Bordetella pertussis, the causative agent of human whooping cough, or pertussis, is an obligate human pathogen with diverse high-affinity transport systems for the assimilation of iron, a biometal that is essential for growth. Under iron starvation stress conditions, B. pertussis produces the siderophore alcaligin. The alcaligin siderophore gene cluster, consisting of the alcABCDERS and fauA genes, encodes activities required for alcaligin biosynthesis, the export of the siderophore from the cell, the uptake of the ferric alcaligin complex across the outer membrane, and the transcriptional activation of alcaligin system genes by an autogenous mechanism involving alcaligin sensing. The fauA gene encodes a 79-kDa TonB-dependent outer membrane receptor protein required for the uptake and utilization of ferric alcaligin as an iron source. In this study, using mixed-infection competition experiments in a mouse respiratory model, inactivation of the B. pertussis ferric alcaligin receptor protein was found to have a profound impact on in vivo growth and survival of a fauA mutant compared with a coinfecting wild-type strain. The attenuating effect of fauA inactivation was evident early in the course of the infection, suggesting that the contribution of ferric alcaligin transport to the ecological fitness of B. pertussis may be important for adaptation to iron-restricted host conditions that exist at the initial stages of infection. Alcaligin-mediated iron acquisition by B. pertussis may be critical for successful host colonization and establishment of infection.